The Attractiveness and Significance of Numerical Number 108 - V. Venkateswara Rao; V. Srinivasa Rao; M. A. Rama Prasad; S. Amarnadh (International Journal of Mathematics And its Applications, 2016)
Numbers are very important role in a daily life.In that, every number having its own importance. Among these numbers, 108 is having much more importance than other numbers and also 108 can be referring in many areas. This manuscript describes the importance of 108 and why people believe 108 is a communicative of the God and the history says 108 can repeat many number of times in different ways. The glories of 108 is it can be expressed in many situation like mathematical, astrology, religions, medical, human body, relationship between human body and god and importance of time.